PENERAPAN METODE MUROJA’AH DALAM MENINGKATKAN HAFALAN AL-QUR'AN - Kamal Maruapey; Uswatun Khasanah; S Sulistyowati; Meti Fatimah (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
The purpose of this study is to find out, 1) how the application of the muroja'ah method in SD Muhammadiyah Palur, 2) what are the obstacles and solutions to the application of the muroja'ah method in SD Muhammadiyah Palur. Muhammadiyah Elementary School Palu. This type of research is qualitative using a narrative approach, namely data obtained from the scene and the informants. Data collection techniques were obtained from interviews, observation and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The data validity technique uses technical triangulation, original triangulation, and time triangulation. This study explains about the muroja'ah system in SD Muhammadiyah Palur, namely, 1) muroja'ah together and being listened to by assatidz, 2) muroja'ah with friends. Constraints in the application of the muroja'ah method are, 1) students are not focused, 2) students are lazy, 3) the environment is less effective. The solutions in overcoming the obstacles in implementing muroja'ah are, 1) the teacher must be creative in teaching, 2) the teacher must understand the characteristics of each student, 3) each student has a rote book and also muroja'ah. The results of the application of the muroja'ah method in SD Muhammadiyah in memorizing the Qur'an are students have confidence in adding to the memorization of the Qur'an and also students are able to complete memorizing the Qur'an. one in juz. 30 and take the tahfidz exam in one sitting.